Les maisons de chefferie du Mbam (Cameroun) - Christian Seignobos; Henri Yambéné Bomono (Afrique Archéologie Arts, 2024)
The Mbam chieftaincy houses, built from 1920 till the end of 1930, were put in place thanks to the colonial administration, who sought to reinforce the power of the chiefs they appointed in societies that lacked such power. The buildings were modelled on the grand colonial mansions of the early 20th century, with a single floor surrounded by a veranda, usually supported by arches or brick pillars. Access to the first floor is via a monumental staircase. These buildings also led to the rise of different trades that will influence all local architectures. Nowadays, the presence of these buildings indicates places of power. On these sites, the right-holders seek to build as close as possible to these houses, or to what remains of them. This, to show their kinship with the deceased chiefs and, consequently, their level of chieftaincy claim or to local or even national representation of their community.